(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Traditional medicines including Ayurveda, Unani have been used as therapeutics in the Indian subcontinent since 5000 BC. Because of the abundance of secondary metabolites, medicinal plants are becoming priceless natural resources for better drug development. Till date almost no ethnopharmacological evidences were available on Colocasia genus except Colocasia esculenta. As a part of our continuing assessment of evidence based use of traditional medicine, we have identified bioactive polyphenols in the ethanolic leaves extract of Colocasia affinis Schott using HPLC-DAD method and evaluated its anti-allergy, anti-inflammatory and anti-diabetic potentials for the first time. Chromatographic investigation showed the presence of p-coumaric acid, trans-ferulic acid, rosmarinic acid, myricetin and kaempferol in the leaves extract. Pharmacological profile exploration demonstrated its anti-inflammatory activity at a dose of 250- and 500-mg/kg in xylene-induced ear edema in mice. The extract significantly reduced the allergy like symptoms such as sneezing, scratching, rhinorrhea, redness and swelling in Tolune diisocyanate (TDI) sensitized allergy model mice at 250- and 500-mg/kg doses. Besides, the extract also exhibited reduction in the level of neutrophils, lymphocytes and eosinophils in a dose dependent manner in the experimental animal. The extract also confirmed reduction of blood glucose levels in the experimental mice at a dose of 250- and 500-mg/kg. Therefore, it is evident that C. affinis demonstrated possesses medicinal values through its anti-inflammatory, anti-allergic and anti-hyperglycaemic potentials. Bangladesh Pharmaceutical Journal 24(1): 1-10, 2021